Premigration exposure to political violence and perpetration of intimate partner violence among immigrant men in Boston. - Gupta, Jhumka; Acevedo-Garcia, Dolores; Hemenway, David; Decker, Michele R; Raj, Anita; Silverman, Jay G (American journal of public health, 2009)
We examined associations between premigration political violence exposure and past-year intimate partner violence (IPV) perpetration among immigrant men attending community health centers in Boston.
Keywords: Adolescent; Adult; Boston; Community Health Services; Confidence Intervals; Cross-Sectional Studies; Domestic Violence; Emigrants and Immigrants; Humans; Male; Odds Ratio; Politics; Prevalence; Questionnaires; Risk Factors; Stress, Psychological; Time Factors; Violence; Young Adult